Strategy-focused requirements engineering method for web applications. (9th July 2007) - Al-Salem, Lana S.; Abu-Samaha, Ala M.
The Web-based Business Applications concept goes well beyond e-commerce, e-banking and e-business as it encompasses the business strategies and processes of the organisation. In this context, aligning web application requirements to the organisation's business strategy is as important as the functional requirements of these applications. The paper presents an Extended Web Application Requirements Engineering (eWARE) method that is strategy-focused to align requirements to business strategy and to elicit legal, technological, business, marketing and content requirements. eWARE is an adaptation of two methods: Viewpoint-oriented Requirements Definition (VORD) to elicit web applications requirements and Balanced Scorecard (BSC) to aid in planning/analysing a business strategy.